ДО ПРОБЛЕМИ ФОРМУВАННЯ ПРОФЕСІЙНОЇ КОМПЕТЕНТНОСТІ МАЙБУТНІХ УЧИТЕЛІВ У КОНТЕКСТІ БОЛОНСЬКОГО ПРОЦЕСУ (Педагогіка вищої та середньої школи, 2006)
This article considers the problem o f the formation of the professional competence o f a teacher in the context o f Boulogne process, the reasons o f modernization of Ukrainian higher education are analyzed.